Analisis Risiko Pembiayaan Bank Syariah - Ilyas, Rahmat (BISNIS, 2019)
Financing or financing is funding provided by one party to another party to support the planned investment, whether done alone or in an institution. Risk in the banking context is a potential event, both predictable and unpredictable that has a negative impact on bank income and capital. The main reason for the occurrence of credit risk is that banks are too easy to lend or invest because they are too required to take advantage of excess liquidity, so that credit assessments are less careful in anticipating various possible business risks that they finance. Risk management is needed to identify, measure and control various types of risk, because it becomes a very basic tool to support the sustainability of the bank's business. The type of risk management that is closely related to the role of DPS is reputation risk, which in turn has an impact on displaced commercial risk, such as liquidity risk and other risks. The function and role of DPS in Islamic banks has strong relevance to the risk management of Islamic banking, namely reputation risk, which in turn impacts other risks such as liquidity risk.